O plano de inovação na rede municipal de Porto Alegre: um estudo em busca das transformações pedagógicas - Pedroso, Maria Carolina Ribeiro (Universidade do Vale do Rio dos Sinos, 2025)
Given the contemporary challenges of public education and the need to align school practices with the cultural, social, and technological transformations of the 21st century, it becomes essential to understand how public policies aimed at innovation materialize in the daily life of schools. This study aimed to analyze how the Innovation Plan of the Municipal Department of Education of Porto Alegre (SMED) contributed to pedagogical innovation in municipal schools. The theoretical framework of the research addresses concepts of pedagogical innovation based on authors such as Cunha (2022), Moraes (1996), Fino (2011), and Behrens (1999), who understand innovation as an paradigm shift with traditional teaching models. Contributions from cyberculture to education are also discussed (Lévy, Lemos, Santos), along with emerging paradigms that emphasize autonomy, critical thinking, and collaborative practices in the teaching-learning process. The research adopted a qualitative and exploratory approach, using a case study in four schools. Document analysis, semi-structured interviews with principals and innovation coordinating teachers, and direct observation of innovation rooms were conducted. The collected data were analyzed using Bardin’s (2016) content analysis method, identifying patterns and thematic categories. The study revealed that the role of the Innovation and Technology Coordinating Teacher has been effective in promoting innovative practices, especially in mediating subjectivities and fostering more welcoming learning environments rooted in emotional dimensions of learning, while breaking away from traditional teaching models and encouraging more active approaches. Additionally, the Innovation Rooms proved to be promising spaces for experimenting with new pedagogical approaches, expanding learning possibilities and increasing student engagement. The results also indicated persistent challenges, highlighting the need for more participatory learning proposals, with greater community involvement through mechanisms of dialogue and consultation.
Keywords: Inovação pedagógica; Ruptura paradigmática; Cibercultura; Professor articulador de inovação; Salas de inovação; Gestão educacional; Pedagogical innovation; Paradigm shift; Cyberculture; Innovation coordinating teacher; Innovation rooms; Educational management; ACCNPQ::Ciências Humanas::Educação